2007
DOI: 10.1300/j236v11n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Using the Arts to Challenge Hate, Create Community: Laramie Lives in Lowell

Abstract: This paper describes a production of Moises Kaufman's The Laramie Project staged at a northeast public urban university and a related educational campaign. Project goals were to discourage homophobia, encourage dialogue, and increase visibility and acceptance of gay, lesbian, bisexual, and transgendered students. The project was produced by a coalition including student groups, academic departments, and administrative units. A variety of indices show the play was immediately successful for the audience and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These authors advocate use of metadialogues as a tool to talk about what individuals might be distancing themselves from or remaining silent about. Others advocate use of role playing, improvisational story-telling, and reader's theatre as mechanisms by which to share stories when students may be reluctant to think differently about the world, and to enact empathic failures and reveal defenses and resistances (Belliveau, 2007;Edmiston, 2000;Iverson, in press;Mulvey & Mandell, 2007;Pincus, 2001). Role playing might allow students to perform a character who says things they feel nervous about saying, permits them to flout the rules, and invites creative and playful transgressions of social norms (Griffiths, 2007).…”
Section: Managing Riskmentioning
confidence: 99%
“…These authors advocate use of metadialogues as a tool to talk about what individuals might be distancing themselves from or remaining silent about. Others advocate use of role playing, improvisational story-telling, and reader's theatre as mechanisms by which to share stories when students may be reluctant to think differently about the world, and to enact empathic failures and reveal defenses and resistances (Belliveau, 2007;Edmiston, 2000;Iverson, in press;Mulvey & Mandell, 2007;Pincus, 2001). Role playing might allow students to perform a character who says things they feel nervous about saying, permits them to flout the rules, and invites creative and playful transgressions of social norms (Griffiths, 2007).…”
Section: Managing Riskmentioning
confidence: 99%
“…Overall, the results are congruent with the review of the literature that show how an intervention can be used to change beliefs and increase positive attitudes towards a variety of different groups of people. Past literature referenced utilization of media such as documentaries, videos, workshops, and plays to address inequality within the LGBTQ+ community (Mizock et al, 2017;Mulvey and Mandell, 2007;White Hughto et al, 2017). This study showed that a 42minute episode of a fictional show, which is something that can be easily more accessible and possibly more appealing to the wider population, brought about a statistically significant change in beliefs and positive attitudes toward transgender people.…”
Section: Discussion Of Resultsmentioning
confidence: 71%
“…There are no data supporting that it was the play itself as opposed to any other activity or combination of activities that resulted in the change. Mulvey and Mandell (2007) looked at how the same play could be used to discourage homophobia, increase dialogue, and increase visibility and acceptance of LGBTQ+ students.…”
Section: Social Justicementioning
confidence: 99%
“…The latter has been found as an effective way to foster growth‐oriented encounters, such that audiences can engage constructively with difference while critically reflecting on their own power, privilege, and positioning. For instance, Mulvey and Mandell (2007) demonstrate how community audiences of The Laramie Project in Lowell, Massachusetts came to question their behaviors toward intolerance and the structures that sanction injustice toward LGBTQ people.…”
Section: Introductionmentioning
confidence: 99%